2000
DOI: 10.1016/s0166-6851(00)00313-3
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Plasmodium falciparum malaria is traced by mitochondrial DNA

Abstract: The origin and geographical spread of Plasmodium falciparum is here determined by analysis of mitochondrial DNA sequence polymorphism and divergence from its most closely related species P. reichenowi (a rare parasite of chimpanzees). The complete 6 kb mitochondrial genome was sequenced from the single known isolate of P. reichenowi and from four different cultured isolates of P. falciparum, and aligned with the two previously derived P. falciparum sequences. The extremely low synonymous nucleotide polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
89
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(99 citation statements)
references
References 30 publications
9
89
0
1
Order By: Relevance
“…Staining the mitochondrion of PbGFP APICO parasites with the mitochondrial-specific dye MitoTracker ® Red CMXRos, showed that the position of the mitochondrion relative to the apicoplast varied in different sporozoites, with the two organelles sometimes lying closely besides each other ( Figures 2D and S2B) and in other sporozoites being clearly distinct ( Figure 2E and Supplementary Figures S2C-S2E). We observed that Hoechst 33342, in addition to staining the sporozoite nucleus, also weakly stained the apicoplast of sporozoites ( Figure 2D), but we never observed DNA staining of the mitochondrion (Conway et al, 2000), perhaps because the mitochondrial genome is only 6 kb compared with 35 kb for the apicoplast.…”
Section: Mosquito-stage Parasite Morphology Of the Apicoplast And Mitmentioning
confidence: 73%
“…Staining the mitochondrion of PbGFP APICO parasites with the mitochondrial-specific dye MitoTracker ® Red CMXRos, showed that the position of the mitochondrion relative to the apicoplast varied in different sporozoites, with the two organelles sometimes lying closely besides each other ( Figures 2D and S2B) and in other sporozoites being clearly distinct ( Figure 2E and Supplementary Figures S2C-S2E). We observed that Hoechst 33342, in addition to staining the sporozoite nucleus, also weakly stained the apicoplast of sporozoites ( Figure 2D), but we never observed DNA staining of the mitochondrion (Conway et al, 2000), perhaps because the mitochondrial genome is only 6 kb compared with 35 kb for the apicoplast.…”
Section: Mosquito-stage Parasite Morphology Of the Apicoplast And Mitmentioning
confidence: 73%
“…(20), and in the mitochondrial genome (21,22). Consistent with the scarce synonymous variation in the Csp of P. vivax (Table 2), Leclerc et al (8) found no variation at all in 12 microsatellite loci (and limited variation at a 13th locus) in 108 samples of P. vivax from eight localities in Asia, Africa, South America, and New Guinea; even less microsatellite variation than in P. falciparum (23), although microsatellite polymorphisms arise at high rates by replication spillage.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Mitochondrial haplotypes, at least for P. falciparum, cluster according to the geographic origin of the samples. 19,20 (3) Most genetic polymorphisms in the mitochondrial genome are evolutionarily neutral and may reflect the population history of lineages more precisely than those genetic polymorphisms in antigen-coding genes. (4) Several hundreds of complete mitochondrial genome sequences from worldwide-collected P. vivax are currently available in public databases.…”
Section: Introductionmentioning
confidence: 99%